Strengthening e-waste governance: A decision framework for sustainable transboundary movements under the Swiss-Ghana Amendments - Mohamed Sultan, Al Amin; Faradillah, Pursatul; Samat, Khairul Fadzli; Kamarulzaman, Thahirah (KeAi Communications Co., 2025)
The Swiss-Ghana Amendments to the Basel Convention mark a significant milestone in global e-waste (electronic waste) management, requiring Prior Informed Consent (PIC) for all transboundary movements of Waste Electrical and Electronic Equipment (WEEE), regardless of their hazard classification. However, developing nations encounter substantial challenges in adhering to these amendments due to regulatory gaps, limited infra‐ structure, and an increasing influx of illicit e-waste imports. This study uses Malaysia as a case study to evaluate the readiness of developing nations to implement amendments, highlighting transferable solutions and recommendations. This study employs a mixed-methods approach that combines qualitative thematic analysis and bibliometric mapping to analyze academic literature, official reports, and international case studies. The findings reveal that while Malaysia has foundational policies in place, significant challenges remain in addressing informal recycling practices, improving enforcement mechanisms, and building the institutional capacity to implement PIC procedures effectively. This study identifies key areas for improvement, including regulatory reforms, infrastructure development, and enhanced monitoring systems. To address these issues, this study proposes a six-key Integrated Decision Framework that emphasizes legislative and regulatory updates, infrastructure development, international cooperation, capacity building and training, public awareness and engagement, and robust monitoring and enforcement mechanisms. Although tailored to Malaysia, the framework offers transferable solutions to align e-waste management systems with the Swiss-Ghana Amendments, providing a pathway for developing nations to strengthen regulatory readiness, mitigate environmental risks, and contribute to global sustainability.